2017
DOI: 10.1111/jocd.12307
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of skin pigmentation by confocal microscopy: Influence of solar exposure and protection habits on cutaneous hyperchromias

Abstract: The data showed the importance of sun protection for preventing changes in the pattern of skin pigmentation, and RCM proved to be an important tool for skin characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 24 publications
0
19
0
2
Order By: Relevance
“…The morphological characteristics observed were consistent with subclinical lentiginous change: hyper‐reflective basal cells around a non‐reflective papillary dermis and increased numbers of dermal papillae. It suggests an early photoaging process as solar lentigo appears after chronic UV exposure and is commonly seen on skin of people > 50 years of age . It was possible to observe reduction in melanin accumulation after 60 days in the UV‐VIS group (Figure B) when compared to the beginning of the study (Figure A).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The morphological characteristics observed were consistent with subclinical lentiginous change: hyper‐reflective basal cells around a non‐reflective papillary dermis and increased numbers of dermal papillae. It suggests an early photoaging process as solar lentigo appears after chronic UV exposure and is commonly seen on skin of people > 50 years of age . It was possible to observe reduction in melanin accumulation after 60 days in the UV‐VIS group (Figure B) when compared to the beginning of the study (Figure A).…”
Section: Resultsmentioning
confidence: 88%
“…As it is known that solar exposure can induce the appearance of hyperchromias, the volunteers were questioned about their habits of solar exposure and protection to reduce the variation factors of the study. None of the volunteers declared changes in their habits during the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of our research group showed the importance of sun protection comparing groups with and without sun protection habits. Martini and collaborators (2017) showed that young women which had high sun exposure and no daily habit of sunscreen use, had more and larger hyperpigmented spots when compared to participants that had lower frequency of sun exposure, as well as daily habits of sunscreen use .…”
Section: Discussionmentioning
confidence: 99%